Regions outside the DNA-binding domain are critical for proper in vivo specificity of an archetypal zinc finger transcription factor. Issue 1 (6th October 2013) - Burdach, Jon; Funnell, Alister P. W.; Mak, Ka Sin; Artuz, Crisbel M.; Wienert, Beeke; Lim, Wooi F.; Tan, Lit Yeen; Pearson, Richard C. M.; Crossley, Merlin
Abstract: Transcription factors (TFs) are often regarded as being composed of a DNA-binding domain (DBD) and a functional domain. The two domains are considered separable and autonomous, with the DBD directing the factor to its target genes and the functional domain imparting transcriptional regulation. We examined an archetypal zinc finger (ZF) TF, Krüppel-like factor 3 with an N-terminal domain that binds the corepressor CtBP and a DBD composed of three ZFs at its C-terminus. We established a system to compare the genomic occupancy profile of wild-type Krüppel-like factor 3 with two mutants affecting the N-terminal functional domain: a mutant unable to contact the cofactor CtBP and a mutant lacking the entire N-terminal domain, but retaining the ZFs intact. Chromatin immunoprecipitation followed by sequencing was used to assess binding across the genome in murine embryonic fibroblasts. Unexpectedly, we observe that mutations in the N-terminal domain generally reduced binding, but there were also instances where binding was retained or even increased. These results provide a clear demonstration that the correct localization of TFs to their target genes is not solely dependent on their DNA-contact domains. This informs our understanding of how TFs operate and is of relevance to the design of artificial ZF proteins.